A facile fluorescent probe based on anthraldehyde for trace Fe(iii) ion determination in neutral aqueous solution. Issue 1 (2nd December 2014) - Huang, Dawei; Gao, Zhuping; Yi, Hao; Bing, Yongxin; Niu, Chenggang; Guo, Qingwei; Lai, Cui
Abstract : A flexible fluorescent probe was synthesized for the determination of Fe(iii ) in aqueous solution by conjugating 4-aminoacetophenone into 9-anthraldehyde. Abstract : A flexible fluorescent probe for the determination of Fe(iii ) in aqueous solution was designed and synthesized by conjugating 4-aminoacetophenone into 9-anthraldehyde as a fluorophore. Its sensing behavior toward metal ions was investigated by fluorescence spectroscopy. The fluorescence intensity of the fluorescent probe decreased with the increasing concentration of Fe(iii ) when it was excited at λ ex / λ em = 402/560 nm in water–ethanol (21.5/3.5, v/v) solutions at pH = 7.20. In addition, the calibration curve was linear in the concentration range of ca. 5 × 10 −9 to 1 × 10 −7 mol L −1 . The prepared dye presented satisfactory sensitivity, and the detection limit could be as low as 3.04 × 10 −10 mol L −1 . The Fe(iii )-selective quenching was insensitive to the presence of Cr(iii ), Cd(ii ), Cu(ii ), Co(ii ), Ni(ii ), Mn(ii ), Ba(ii ), Pb(ii ), Ca(ii ), Fe(ii ), Zn(ii ), Mg(ii ), and Al(iii ). The proposed method was successfully employed for preliminary application in natural water, domestic sewage, and human serum samples.